The study´s goal is establish relationships among different variables of the ENOPu-06.It analyzes the relationship among education level and the health center to visit thelast time, family revenue and region of residence and finally, age and health centervisited the last time. Through an analysis of correspondence it was established thatpeople with most age prefer local attention. The people from the metropolitan regionhave a revenue high enough to satisfying their needs. People with high educationallevel do visit hospital or health center with more special service - Aguilar Fernández, Eduardo (2011)
The study´s goal is establish relationships among different variables of the ENOPu-06. It analyzes the relationship among education level and the health center to visit the last time, family revenue and region of residence and finally, age and health center visited the last time. Through an analysis of correspondence it was established that people with most age prefer local attention. The people from the metropolitan region have a revenue high enough to satisfying their needs. People with high educational level do visit hospital or health center with more special services